Effects of Chromium Picolinate on Weight Gain, Selected Blood Metabolites, Leptin and Immunity in Calves - Uyanik, Fatma; Guclu, Berrin Kocaoglu; Sahna, Kezban Can; Bilge Dagalp, Seval; Erdem, O. (Medwell Online, 2008)
This study was performed to investigate the effects of chromium picolinate (CrPic) on weight gain, some blood variables including leptin and to evaluate whether there is any relationship between leptin and immune response in chromium supplemented non-stressed calves. Twenty-four. Holstein calves evenly divided into 3 groups. The age of the calves ranged from 6 to 8 weeks and their initial weight were 76.17 +/- 8.56 kg. Calves received orally either 0, 200 or 400 mu g Cr/calf/day for 12 weeks in the form of CrPic. Calves in all groups were offered a commercial starter and grower diets ad libitum up to 2.5 kg and alfalfa hay and water were provided ad libitum. Animals were vaccinated with inactivated IBR-marker vaccine (Bayovac-Bayer) at 6 and 9th weeks of the experiment. The weight of the animals was recorded and weight gain was calculated. Blood samples were collected on 21 at days of both vaccinations for determination of primary and secondary antibody responses. Sera were analysed for serum total protein, albumin, glucose, iron, chromium and leptin. Supplementation of 200 and 400 mu g Cr/calf/day slightly increased weight gain and significantly enhanced the primary and secondary antibody responses against IBR-marker vaccine in the calves without effecting blood leptin and other serum variables. Supplementation of 400 mu g Cr/calf/day had no further improvement in immune response, therefore a daily supplementation of 200 mu g chromium may be recommended to enhance the efficacy of vaccination in calves in the field conditions.
Keywords: Calves; chromium; immunity; leptin; blood metabolites; weight gain